Hewlett Packard: a pioneering approach to global account management - Yip, George S. (Henry Stewart Talks, 2018)
This case study describes Hewlett-Packard’s global account management programme and its evolution since the 1990s. Today, Hewlett-Packard uses an extensive, multi-tiered global account management programme which it sees as essential for the retention of its most important multinational customers.